New species and new records of Indonemoura (Plecoptera: Nemouridae) from Xizang of southwestern China - Liu, Dongxia; Yang, Ding; Li, Weihai (Zootaxa, 2024)
A new species of stonefly (Plecoptera: Nemouridae), Indonemoura sejila sp. n., is described from the Xizang Autonomous Region and the affinities towards a similar species, I. nigrihamita concava Li & Yao, 2017, is discussed. Indonemoura geminus Zwick, 1977 and I. indica (Kimmins, 1947) are recorded from China for the first time.